FOREIGN EXPERIENCES OF INCREASING INVESTMENT ACTIVITY IN SMALL INDUSTRIAL ZONES AND OPPORTUNITIES FOR THEIR USE - Shakhnoza Elshodovna Mannapova (Western European Studies, 2025)
The article examines foreign experiences of increasing investment activity and the possibilities of their use. The urgent importance of increasing investment activity is focused on the full use of the advantages and characteristics of the industrial potential of the region. In the Chinese experience of increasing investment activity in industrial zones, the main aspects that take into account the economic potential of each region are highlighted.
Keywords: small industrial zones; investment program; investment project